Concrete retrofitting using metakaolin geopolymer mortars and CFRP - Vasconcelos, E. (2011)
This paper presents results about the use of metakaolin based geopolymers mortars for retrofitting purposes. Two main situations are addressed, the use of geopolymeric mortars as a repairing layer or as a binding agent to insure the adhesion between CFRP sheets and the concrete substrate. Several compositions of metakaolin geopolymer mortars were executed by varying the percentage of sand/binder mass ratio and the concentration of sodium hydroxide. It was found that metakaolin geopolymer mortars show a high mechanical resistance and a relevant adhesion to the concrete substrate. Although their adhesion strength is lower than the one present by commercial pre-pack repair mortars, they are very cost-effective (5 to 10 times less expensive). On the other hand, the adhesion strength between CFRP and geopolymer mortars proved to be lower than expected which could be due to the fact that the composition of the geopolymeric mortars was not optimized and also to the fact that the CFRP used was not prone to this kind of application.